Ответ:
(2; 3)
Пошаговое объяснение:
{х/5 - у/3 + 0,6 = 0 | * 15
{х/4 + у/6 - 1 = 0 | * 12
{3х - 5у + 9 = 0
{3х + 2у - 12 = 0
{3х - 5у = -9 | * -1
{3х + 2у = 12
{-3х + 5у = 9
{7у = 21
1)
7у = 21
у = 21 : 7
у = 3
2)
3х + 2у = 12
3х + 2 * 3 = 12
3х + 6 = 12
3х = 12 - 6
3х = 6
х = 6 : 3
х = 2
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
(2; 3)
Пошаговое объяснение:
{х/5 - у/3 + 0,6 = 0 | * 15
{х/4 + у/6 - 1 = 0 | * 12
{3х - 5у + 9 = 0
{3х + 2у - 12 = 0
{3х - 5у = -9 | * -1
{3х + 2у = 12
{-3х + 5у = 9
{3х + 2у = 12
{7у = 21
{3х + 2у = 12
1)
7у = 21
у = 21 : 7
у = 3
2)
3х + 2у = 12
3х + 2 * 3 = 12
3х + 6 = 12
3х = 12 - 6
3х = 6
х = 6 : 3
х = 2